GURU PENGGERAK: PELUANG, TANTANGAN, DAN ARAH PENGEMBANGAN DI INDONESIA - Dewiyana Agustina; Dinie Anggraeni Dewi; Tuti Istianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Guru Penggerak Program aims to enhance the quality of education in Indonesia by developing the role of teachers as learning leaders. This article addresses the issue of the limited leadership role of teachers within educational communities, which hinders educational transformation at the local level. The study aims to analyze the opportunities, challenges, and developmental directions of the Guru Penggerak Program based on the author's experiences in various roles within the program, ranging from practice instructors to facilitators in intensive areas such as Papua. The methodology used is a reflective-descriptive approach based on empirical experiences. The analysis focuses on the dynamics of program implementation, encompassing aspects of training, field application, and the response of educational communities. The findings reveal that the program offers opportunities to enhance pedagogical competence, leadership skills, and school cultural transformation. However, the program faces challenges such as participants' capacity gaps, resistance to change, and geographical and infrastructural constraints, especially in remote areas. This article provides recommendations, including strengthening local support, increasing technological capacity, conducting continuous evaluations, and reinforcing alumni networks for program sustainability. It contributes to offering comprehensive insights to support the development of more effective educational policies and practices in Indonesia.